ANALISIS KETERAMPILAN PROSES SAINS TENTANG GERAK HARMONIS PESERTA DIDIK KELAS X SMA - Indah Sulastri; Stepans Sahala; Syukran Mursyid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to analyze the science process skills about the harmonic motion of the tenth graders of SMA N 1 Anjongan. The form of research used is survey research..The sampling technique in this study was census/total sampling. The sample in this study were all students of class X IPA totaling 70 people. The test used in the form of a science process skills test in the form of multiple choice as many as 16 questions that have met the aspects of science process skills. This test is given to measure students scientific process skills in solving problems about harmonic motion. The results of the research analysis showed that the average percentage of students' science process skills was 59.11% in the less category. The percentage aspects of science process skills include: observation of 73.57%, classification of 64.29%, interpretation of 60.71%, prediction of 63.57%, communication of 58.57%, planning experiments of 50.00 %, applying the concept of 46.43%, and 51.43% hypothesized. Based on the Mann-Whitney test, the sig value is obtained. (2-tailed) 0.568 <0.05, which means that there is no difference in students' science process skills between boys and girls.Keywords: Analysis, Science Process Skills, Harmonic Motion